The Influence of the Inquiry Method on Students' Understanding Ability in Science Subjects in Class V of SD Muhammadiyah 19 Medan - Sari, Tiara Erlinda; Elfrianto, Elfrianto (Holistic Science, 2025)
This study aims to analyze the effect of the inquiry method on students' understanding in science subjects in grade V of SD Muhammadiyah 19 Medan. This study uses a quantitative approach with a purposive sampling technique involving 47 students from two classes, namely the experimental class that applies the inquiry method and the control class that uses the conventional method. Data collection was carried out through an understanding test before (pre-test) and after (post-test) learning. Hypothesis testing uses a t-test after going through the analysis prerequisite test (normality and homogeneity tests). The results showed that the inquiry method had a significant effect on students' understanding with a significance value of 0.000 (<0.05). The average score of students' understanding in the experimental class reached 83.08%, higher than the control class which only obtained 72.36%. These findings indicate that the inquiry method can improve students' understanding effectively compared to conventional methods. Therefore, the application of the inquiry method is recommended as an alternative learning strategy in improving the quality of students' understanding in science subjects.